(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2020)
The aim of this paper is to predict the hemodynamics properties of blood flow during in the Critical stenosis RCA . This paper examines pulsed , laminar blood flow through state of the right coronary artery in patient heart. Data for these case were taken from a catheter laboratory in the Thi Qar Heart Center . The case for a man born in 1957 who has one stenosis in RCA with a stenosis of 80%. A non-Newtonian blood model characterized by the Carreau equation was used, and a 3D model was used with the governing equations analyzed using the specified volumetric method. The SIMPLE algorithm has been adopted to link pressure and speed during runoff. Geometric figures are drawn using Auto CAD software and combined with FLUENT. The results showed that the speed increased significantly in the area of stenosis. Non-Newtonian viscosity increases its effect near the center of stenosis. The total pressure is equal to diastolic pressure with little increase